Grain size analyses and organic matter content of bottom sediment sampled along the French Mediterranean coast in 2012 - Briz Parent; Christine Barras; Erica Bicchi; Éric Bénéteau; Annick Donnay; Corinne Pelaprat; Frans J Jorissen (PANGAEA, 2021)
The stations were sampled along the French Mediterranean coast in spring (March-April) 2012 onboard the RV Europe. Bottom sediment at 36 stations (10 to 71 m water depth) was sampled using a Reineck box-corer. Three replicates (“a”, “b”, “c”; different box-corer launches) were done at each station for meiofauna analysis. The surface sediment (0-1 cm) of the first box-corer launches (i.e., “a”) was used for grain size analysis. If the sediment appears visually very different in the second and third launches (i.e., “b” and “c”) another sample was taken. Sediment was sampled from the three replicates box-corer and gathered to measure grain sizes thanks to sieves. Sediment samples were first dry weighted, then wet sieved on 63, 125, 150, 250, and 500 μm meshes and finally residues were dry weighted. Then, the percentage from the total dry weight was calculated for each size fraction. Sediment from a Van Veen grab launch, deployed at each station, was used to measure organic matter content. The organic matter percentage was determined with the loss on ignition method, 4h30 at 450 °C. Missing values means not available. These data were acquired thanks to Pierre Boissery and the funding from the Agence de l extquotesingleEau Rhône Méditerranée Corse. The sampling survey was possible thanks to the Ifremer, especially Bruno Andral, and the RV Europe crew members.